2018
DOI: 10.1016/j.acvd.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between multipolar mapping and conventional mapping of atrial tachycardias in the context of atrial fibrillation ablation

Abstract: In patients with multiple ATs, multielectrode PentaRay mapping was faster than the conventional technique, with less radiofrequency delivery and a better mid-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
9
0
6
Order By: Relevance
“…However, few studies have compared multipolar with conventional PbyP mapping. Bun et al 23 reported a significant reduction in mapping and ablation times with MPM using the PentaRay for macro (69%) and focal AT following AF ablation. Arrhythmia recurrence was significantly less in the MPM group, however, the historical PbyP control group had all undergone ablation in a time period earlier than the MPM 23 and there was a significant difference in the incidence of focal tachycardias between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have compared multipolar with conventional PbyP mapping. Bun et al 23 reported a significant reduction in mapping and ablation times with MPM using the PentaRay for macro (69%) and focal AT following AF ablation. Arrhythmia recurrence was significantly less in the MPM group, however, the historical PbyP control group had all undergone ablation in a time period earlier than the MPM 23 and there was a significant difference in the incidence of focal tachycardias between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…If a higher mapping density was expected with the multipolar catheter, 42 several other results 41 emphasize the importance of smaller size-closely-spaced electrodes when mapping scar-related AT. In these conditions, EGM duration is shorter (by eliminating far-fields and minimizing the mapped area by each point), delineation of lowvoltage areas is improved (abnormal, low-voltage, as well as densescar areas are smaller), late potentials and EGM fractionation are more frequently recorded.…”
Section: Preprocedural Imagingmentioning
confidence: 92%
“…The use of the PentaRay catheter has been demonstrated in a number of case reports and studies of patients with AF. [19,20,34,42,43] In a recent prospective study – Substrate Ablation Guided by High Density Mapping in Atrial Fibrillation (SUBSTRATE HD) (NCT02093949), AF was sequentially mapped in both atria of 105 patients admitted for AF ablation, using the PentaRay catheter. Radiofrequency times and procedure times were shorter with the PentaRay catheter compared with a validation set in which a conventional ablation approach was used.…”
Section: The Multipolar Mapping Catheter As a Tool For Substrate Mappmentioning
confidence: 99%